PENGARUH GREEN MARKETING DAN GREEN PRODUCT TERHADAP MINAT BELI AIR MINERAL DALAM KEMASAN LE MINERALE PADA MASYARAKAT KOTA MEDAN - Sitorus, Yvandrew Phillip Michael; Nasution, Amrin Mulia Utama (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
Public awareness of environmental issues is increasing, encouraging companies to implement green marketing strategies and present environmentally friendly products (green products) to attract consumer buying interest. This study aims to analyze the influence of green marketing and green products on purchasing interest in Le Minerale brand mineral water in Medan City. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 150 respondents who were people in Medan City who knew or had purchased Le Minerale. The data analysis technique was carried out using multiple linear regression analysis with the help of SPSS. The results showed that green marketing had a positive and significant effect on purchasing interest, with a regression coefficient of 0.412 and a significance value of 0.000. This shows that a marketing strategy that emphasizes environmental sustainability can increase consumer purchasing interest. In addition, green products also have a positive and significant effect on purchasing interest, with a regression coefficient of 0.387 and a significance value of 0.002. However, the influence of green marketing is more dominant than green products in shaping consumer purchasing interest.